Psychosocial Effect of Motivational Incentives on Senior Secondary Schools Teachers’ Work Effectiveness in Adamawa State, Nigeria - Kwaji Tizhe Takwate (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
This study investigated the psychosocial effect of motivational incentives on Senior Secondary Schools teachers’ work effectiveness in Adamawa State, Nigeria. The study adopted survey research design. The population of this study consisted of 162 school administrators and 74 teachers selected from 58 Government owned Senior Secondary Schools in Adamawa State, from a which a sample of 40 respondents were selected using purposive sampling technique. Motivational Incentives and Teachers’ Effectiveness Questionnaire (MITEQ) was used for data collection. The findings of the study revealed that there is lack of service improvement, seminars, and inadequate provision of teaching and learning materials. Teachers are always internally motivated, inconsistent performance evaluation, promotions are not awarded as at when due, and issuance of query letters at slightest provocations by principals. The also revealed that, motivation is the backbone of effective service delivery. This study also revealed that motivational incentive has significant effect on teachers’ work effectiveness and that there is no significant difference between male and female teachers’ reaction and response to motivational incentives. No significant difference was found between different types of motivation incentives and their effect on senior secondary school teachers’ work effectiveness in Adamawa State. The study recommended others that the government as a matter of urgency The study recommends the provision of regular performance enhancement seminars for teachers, adequate provision of teaching and learning materials, prompt payment of teachers’ salary and other monetary incentives and teachers should be internally motivated on the job. For the incentive to have the intended impact on teachers the study recommend that it should be awarded only to those teachers who actually exhibit the intended behaviours and such incentives should be distributed based on collaborative performance rather than on individual performance.